Analysis of Pedestrian Lane Users’ Comfort at Padangsidimpuan - Novrial; Hammi Fadhilah Lubis (Talenta Publisher, 2020)
A convenient pedestrian lane is specifically intended for pedestrians as the main priority. Some factors which influence the comfort of the pedestrian lane are microclimate, noise, aroma, security, cleanliness, beauty. The research was done at the pedestrian lane of Padangsidimpuan by using field observation. The data were obtained from surveying and questionnaire distribution. The research used the descriptive method to describe the existing condition of the pedestrian lane. It based on its comfort and Likert scale calculation to find out the level of comfort of pedestrian lane users. The result of the research showed that the level of comfort from the factor of security, pedestrians’ safety from offense had the highest value of 71%, the level of offense at Padangsidsimpuan was low, and the level of comfort, from the blazing heat, had the lowest value of 41%. It was because shade trees were not densely planted; they were only on the left side of the pedestrian lane so that they did not function optimally. It is recommended that the comfort of the pedestrian lane at Padangsidimpuan be increased and renewed by prioritizing the disabled people, planting trees along the pedestrian lane, and building stopping places to enable pedestrians to wait for public transportation.